Analisis Pengaruh PDRB Infrastruktur Jalan dan Ekspor Terhadap Investasi Asing di Indonesia Studi Kasus 34 Provinsi di Indonesia Tahun 2020-2024 - Tanzil Ariansyah; Siti Hodijah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Analysis of the Effect of GRDP, Road Infrastructure, and Exports on Foreign Investment in 34 Provinces in Indonesia in 2020–2024”. This study aims to analyze and identify the effect of Gross Regional Domestic Product (GRDP), road infrastructure, and exports on foreign direct investment (FDI) in Indonesia at the provincial level. The research method used is a quantitative approach with secondary data obtained from the Central Statistics Agency (BPS) and related agencies. The data used is panel data, namely a combination of time series data for 2020–2024 and a cross section of 34 provinces in Indonesia. The analysis technique used is panel data regression with the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM) approaches, and model selection tests are carried out through the Chow test, Hausman test, and Lagrange Multiplier (LM) test. In addition, classical assumption tests and hypothesis tests are also carried out to ensure the validity of the research results. The results show that GRDP, road infrastructure, and exports have different effects on foreign investment in Indonesia, both partially and simultaneously, depending on the characteristics of each province. This finding indicates that improvements in economic indicators are not always followed by consistent increases in foreign investment in each region.